Isolation of Malassezia pachydermatis and M. sympodialis from the external ear canal of cats with and without otitis externa - Selene, C. E. Dizotti [UNESP]; Coutinho, D. A. [UNESP] (Akademiai Kiado, 2007)
The objective of this study was to determine the presence of Malassezia spp. in the external ear canal of cats with and without otitis. Forty-five animals were studied, 20 with and 25 without otitis externa (OE). Cerumen or secretion from external ear canal samples was cultured on modified Mycosel agar and sterile olive oil was added to the surface of the medium before specimen seeding. The isolates were analysed for macro- and micromorphology and identified by catalase tests and on the basis of growth on Tween 20, 40, 60 and 80. Malassezia spp. were isolated from 15 out of 20 (75%) animals with otitis and from 7 out of 25 (28%) cats without OE; the difference between the two groups was statistically significant (P <= 0.05). Malassezia pachydermatis and M. sympodialis were isolated from 60% (12/20) and 40% (8/20) of cats with otitis, respectively, with no significant difference in the frequency of isolation between the two species. In the microflora of the healthy ear canal M pachydermatis was significantly more common (6/25, 24%) than M sympodialis (1/25, 4%). The present investigation confirms that M sympodialis can also act as an actiological agent of feline OE, and if commercial veterinary laboratories do not use media with added lipids for the isolation of Malassezia spp., this might lead to false-negative results.
Keywords: Malassezia pachydermatis; Malassezia sympodialis; cat; microflora; otitis